Interface engineered silver nanoparticles decorated g-C3N4 nanosheets for textile based triboelectric nanogenerators as wearable power sources. (April 2022) - Bayan, Sayan; Pal, Sourabh; Ray, Samit K.
Abstract: Textile based mechanical energy harvesting devices have emerged out as potential power sources for wearable electronics. For the first time, we report the fabrication of a textile based triboelectric nanogenerator (T-TENG) composed of an active layer of silver (Ag) nanoparticles loaded graphitic carbon nitride (g-C3 N4 ) nanosheets on carbon fibres. The triboelectric characteristics has been found to be dramatically enhanced upon combinatorial effect of Ag nanoparticles loading and interfacial engineering with the introduction of a nylon layer between nanosheets and carbon cloth fibres. With teflon as a counter triboelectric material, under mechanical agitation, the AgCN/nylon bi-layer T-TENG can generate an open circuit voltage of as high as ~ 200 V and charges a commercial capacitor up to ~85 V in only 30 s. The improvement in triboelectric characteristics of the AgCN based bi-layer T-TENG is attributed to Ag nanoparticles induced modifications of surface area, dielectric properties and intrinsic resistivity of the host material. Apart from mechanical impact, the T-TENG can generate electrical output under minute mechanical forces originating from sources like air flow and biomechanical actions when integrated to wearable clothing and the output data can be accessed remotely. The AgCN/nylon-teflon based bi-layer T-TENG is not only stable at higher operating temperatures but also exhibits a higher power conversion efficiency at an elevated temperature (up to ~65 °C), which could be explained by the energetics of the composite system. The superior output characteristics as well as thermal stability of AgCN/nylon based triboelectric nanogenerator makes it a potential candidate for integration into textile based wearable electronic devices. Graphical Abstract: Interface Engineered Silver Nanoparticles Decorated g-C3 N4 Nanosheets for Textile based Triboelectric Nanogenerators as Wearable Power Sources ga1 Highlights: Fabrication of triboelectric nanogenerator with Ag loaded graphitic carbon nitride (g-C3 N4 ) nanosheets on textile platform. Dramatic enhancement of electrical output due to interfacial engineering upon introduction of nylon interfacial layer. Demonstration of triboelectric output generation under air flow and biomechanical actions. Manifestation of g-C3 N4 -textile based triboelectric nanogenerators as self-powered sensors for remote location sensing.